الأمن الإنساني في مجتمع السجن: دراسة تطبيقية على سجن دمو بمحافظة الفيوم - شنب، آية عطية أحمد عبدالرؤف (مؤسسة تواصل للدراسات والتوعية الثقافية, 2024)
شهدت الساحة الدولية العديد من التغيرات التي أسهمت في إعادة بلورة المفاهيم والوسائل التقليدية التي اعتاد عليها العالم في مواجهة الأزمات، وبات مفهوم الأمن التقليدي والمتمثل في الأمن العسكري والحدودي فقط غير قادر على موجة الأخطار الجديدة التي اجتاحت العالم. وتأتي أهمية طرح موضوع الأمن الإنساني في مجتمع السجن كموضوع جديد يتطلب دراسات كثر، تلقى الضوء معرفياً وتطبيقياً على قضية اجتماعية ذات صعوبة بالغة في دراستها لعوامل عدة، تتعلق بطبيعة مجتمع السجن، وآليات التعامل مع محكوم عليهم في قضايا مخلة بالقانون، وإدارة تحكمها أنظمة وقواعد ترتبط بالضبط والربط والحزم، وتتعلق أيضاً بدرجات الوعي لدى كلاً من القائمين على إدارة السجون ومدى إيمانهم بقضايا حقوق الإنسان من جهة، وإدراك المحكوم عليه بحقوقه وواجباته من جهة أخرى. وبناء على ذلك ركزت هذه الدراسة على القضايا التالية: -معايير وشروط الأمن الإنساني داخل السجن -موقف التشريع المصري من حقوق السجين -سياسات إدارة السجن نحو مفهوم الأمن الإنساني ومدى تطبيق المعايير المتعارف عليها. The international arena has witnessed several changes that have contributed to the reformulation of the traditional concepts and means that the world has been accustomed to in facing crises. The traditional concept of security, represented only in military and border security, has become incapable of dealing with the new dangers that have swept the world. The importance of addressing the topic of human security in the prison community as a new topic that requires many studies arises, shedding light theoretically and practically on a social issue that is extremely difficult to study due to several factors related to the nature of the prison community, the mechanisms of dealing with convicts in cases of legal violations, and the management governed by systems and rules related to control, tightening, and firmness. It is also related to the levels of awareness among those in charge of prison management and the extent of their belief in human rights issues on the one hand, and the convict’s awareness of his rights and duties on the other hand. Accordingly, this study focused on the following issues: - Criteria and conditions for human security within the prison - The position of Egyptian legislation on the rights of the prisoner - Prison management policies towards the concept of human security and the extent of application of the recognized standards.
Keywords: المؤسسات السجنية -- الأمن الإنساني -- حقوق الإنسان -- البرامج التأهيلية -- التشريعات المصرية